ASSESSMENT OF INTEREST RATES INFLUENCE ON DEPOSIT MOBILISATION FOR SELECTED SAVINGS AND CREDIT CO-OPERATIVE SOCIETIES IN WESTERN KENYA. - LUVATE, GEOFREY; SANGORO, MR. OSCAR; MWAU, Dr. JONATHAN (IJRDO - Journal of Business Management, 2016)
From an institutional perspective, the primary motive for mobilizing savings lies in lower cost of capital compared to other sources of funds. In Western region, various cooperative societies have been registering losses and even some have gone out of business which has always been ascribed to reduced deposits by their customers. For instance, SACCOs such as Mumias Out growers Sacco Society (MOSSACO) was temporarily closed down in 2009 because of deposits withdrawal by majority of its members thus leaving the SACCO with low capital base to facilitate its operations. The interest rate at the time were at five percent while the one offered on loans were at 15 percent which were considered low on deposits and high on loans. The study design was a descriptive study with comparative design; the study population comprised of employees and customers of selected SACCOS. The study sample size was 293 members. Data collection instruments were questionnaire and interview schedule. Reliability and validity of instrument were done accordingly. Data were analyzed by use of quantitative and qualitative methods to determine the interest rates influence on deposit mobilization of the SACCOS selected for the study. It was found that most of the customers agreed that their knowledge on interest rates has helped them to make savings in their respective SACCOs. This result suggests that trying to influence the SACCOs deposits by manipulating interest rates is not likely to be a practical policy option in western region. However it was recommended that the SACCOs should attempt to maintain competitive positive real interest rates relative to those offered by other financial institutions in order to increase their savings. Further recommendation to use both qualitative and inferential methods of analysis like liner correlations and Carrying out study with SACCOs that have member spread all over the country to refine the findings applicability